2017
DOI: 10.1111/bph.13980
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of acute and anticipatory nausea by peripherally restricted fatty acid amide hydrolase inhibitor in animal models: role of PPARα and CB1 receptors

Abstract: Effective treatments of nausea are limited. In this study we evaluated the ability of the peripherally restricted fatty acid amide hydrolase (FAAH) inhibitor, URB937, to suppress acute and anticipatory nausea in rats and examined the pharmacological mechanism of this effect. EXPERIMENTAL APPROACHWe investigated the potential of URB937 (administered i.p.) to reduce the establishment of lithium chloride-induced conditioned gaping (model of acute nausea) and to reduce the expression of contextually-elicited condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…On the other hand, FAAH inhibition has been found to reduce LiCl-induced nausea when administered systemically ( Rock et al, 2015 ; Parker et al, 2016 ). This effect may be mediated by a peripheral mechanism, since Rock et al (2017) found that the peripherally restricted FAAH inhibitor, URB937, reduced LiCl-induced conditioned gaping, potentially by its action on the area postrema, an area of weakened blood brain barrier. Future research needs to address potential central sites of action of FAAH inhibition in the reduction of nausea.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, FAAH inhibition has been found to reduce LiCl-induced nausea when administered systemically ( Rock et al, 2015 ; Parker et al, 2016 ). This effect may be mediated by a peripheral mechanism, since Rock et al (2017) found that the peripherally restricted FAAH inhibitor, URB937, reduced LiCl-induced conditioned gaping, potentially by its action on the area postrema, an area of weakened blood brain barrier. Future research needs to address potential central sites of action of FAAH inhibition in the reduction of nausea.…”
Section: Discussionmentioning
confidence: 99%
“…Exact structure: endogenous peroxisome proliferator-activated receptor alpha (PPAR-α) agonist (Gaetani et al 2003), antitussive activity (Wortley et al 2017), anti-inflammatory activity (Toguri et al 2018), used to treat post-traumatic stress disorder by fatty acid amide hydrolase (FAAH) inhibition (Danandeh et al 2018), useful in the treatment of neurological disorders (Pandey et al 2018), anti-nausea effect (Rock et al 2017), analgesic activity (Zubrzycki et al 2017), anticancer activity against colon cancer cells (Pagano et al 2017)…”
Section: Resultsmentioning
confidence: 99%
“…While many of the effects exerted by these agents—including reduced anxiety‐, depression‐, and pain‐related behaviours in animal models (Bortolato et al, 2007; Gobbi et al, 2005; Russo et al, 2007)—may primarily depend on increased anandamide activity at cannabinoid receptors, other responses appear to involve the amplification of different FAAH‐regulated lipid signals. For example, endogenous PPAR‐α agonists (most likely PEA and/or OEA) have been implicated in the effects of FAAH inhibition on acute nausea (Rock et al, 2017), cognition (Mazzola et al, 2009; Panlilio et al, 2016), and inflammatory pain (Sagar, Kendall, & Chapman, 2008). Synergistic interactions between CB 1 receptors and PPAR‐α have also been documented (Calignano, La Rana, Giuffrida, & Piomelli, 1998; Russo et al, 2007).…”
Section: Discussionmentioning
confidence: 99%